On the periodicity of composite function - Šapurovas, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Б. Шапуров. О периодичности сложной функции A. Šapurovas. Sudėtinės funkcijos periodiškumo klausimu